Analisis Kesalahan Penggunaan Bahasa Indonesia dalam Penjualan Produk Iklan di Indonesia - Edi Syahputra; Nisa Febriyanti Tanjung; Dwi Fatimah; Asmaul Husna; Winda Aulia (Universitas Dehasen Bengkulu, 2022)
The purpose of this study is to explain Indonesian errors in the field of discourse in Indonesian product advertisements. The ads analyzed are advertisements for food, beverages, cosmetic soaps, etc. This study uses a descriptive approach through two stages, namely data acquisition and data analysis. Indonesian product advertisements using written language were chosen for research. The aim is to analyze Indonesian errors in the field of discourse. The results obtained from this study are one data on the use of reference errors, two data on the use of substitution errors, one data on the invalidity of discourse due to omissions, merge errors, and consistency. data errors that deviate from the Indonesian language rules, and two data ambiguities.